Pengaruh Kompensasi Dan Pengembangan Karir Terhadap Kepuasan Kerja Pada Chigo X Flip Area 3 Jakarta Selatan - Rahma Aji Anggraeni; Henni Marlinah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to find out partially or simultaneously the Influence of Compensation and Career Development on Job Satisfaction in Chigo X Flip Area 3 South Jakarta. The research methodology used is to use quantitative methods. The population in this study is all employees who work at Chigo x Flip Area 3 South Jakarta, which is 105 people. The samples used in this study used random sampling techniques and used the slovin formula to calculate how many samples would be used in the study. The data analysis method uses validity test, reliability test, normality test, multicolinity test, heterokedasticity test, simple linear regression test, multiple linear regression test, correlation coefficient test, determination coefficient test, t test (partial) and f test (simultaneous). The results of the research show that: 1) There is a positive and significant influence between compensation on job satisfaction in Chigo x Flip Area 3 South Jakarta, where the partial t test value that the compensation variable has t calculated 6.356 > t table 2.021 with a significance level of 0.000 < 0.05. 2) There is a positive and significant influence between compensation on job satisfaction in Chigo x Flip Area 3 South Jakarta, where the partial t test value that the compensation variable has a t calculation of 7.050 > t table 2.021 with a significance level of 0.000 < 0.05. 3) There is a positive and significant influence between compensation and career development on job satisfaction in Chigo x Flip Area 3 South Jakarta, where the F test value above is obtained with an F value of 48.888 > F table 3.118 with a significant level of 0.000 < 0.05.